KEBIJAKAN PEMERINTAH INDONESIA MEMBENTUK INDONESIA TRADE PROMOTION CENTRE (ITPC) TERHADAP KOREA SELATAN TAHUN 2012 - Raudah Oktaviani; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research describes the policy of Indonesian Government create a Indonesia Trade Promotion Centre in South Korea in 2012. The trade relationss between Indonesia and South Korea have a big increase. Since 2006 Indonesia and South Korea Government have a deall about the Joint Declaration on Strategic Partnership between Republic of Indonesia and Republic of Korea to Promote Friendship and Cooperation in the 21st Century.The research method used was a qualitative with descriptive as a technic of the research. Writer collects data from books, encyclopedia, journal, mass media and websites to analyze the policy of Indonesian Government create a Indonesia Trade Promotion Centre in South Korea. The theories applied in this research are decisions making policy theory by Viotti and Kaupi and national interest concept from Donald E. NUchterlain.The research shows that policy of Indonesian Government create a Indonesia Trade Promotion Centre in South Korea are becaus defisits of Indoesian export to South Korea and also with create a Indonesia Trade Promotion Centre in South Korea, Indonesia Government can give some information about market brief and market opportunities in South Korea for the Company from Indonesia.Key words: Decision Making, ITPC, Indonesian Policy, Cooperation